A = \(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{2016}-\frac{1}{2017}\)
= \(1-\frac{1}{2017}\)
= \(\frac{2016}{2017}\)
Đúng 0
Bình luận (0)
\(A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{2016}-\frac{1}{2017}\)
\(A=1+\left(-\frac{1}{2}+\frac{1}{2}\right)+\left(-\frac{1}{3}+\frac{1}{3}\right)+...+\left(-\frac{1}{2016}+\frac{1}{2016}\right)-\frac{1}{2017}\)
\(A=1+0+0+...+0-\frac{1}{2017}\)
\(A=1-\frac{1}{2017}\)
\(A=\frac{2017}{2017}-\frac{1}{2017}\)
\(A=\frac{2016}{2017}\)
Vậy: \(A=\frac{2016}{2017}\)
Đúng 0
Bình luận (0)
Cách làm của bạn Sang đầy đủ và chi tiết hơn đó bạn! :) Những bài có quy luật tương tự bạn cũng áp dụng cách giải trên nhé bạn.
Đúng 0
Bình luận (0)